Association between air pollutants and birth defects in Xiamen, China - Huang, Zhimeng; Qiu, Yue; Qi, Jiawen; Ma, Xiaohui; Cheng, Qiliang; Wu, Jinzhun (Frontiers in Pediatrics, 2023)
Abstract: Objective To explore the relationship between common air pollution and common birth defects, and to provide reference for the prevention of birth defects. Methods We conducted a case-control study in Xiamen, a city in southeastern China from 2019 to 2020. Logistics regression was used to analyze the relationship between sulfur dioxide(SO2), fine particulate matter2.5(PM2.5),nitrogen dioxide(NO2), ozone(O3), carbon monoxide(CO) and the occurrence of common birth defects such as congenital heart disease, facial cleft, and finger deformity. Results SO2 significantly increased the risk of birth defects such as congenital heart disease, cleft lip and/or cleft palate, and ear deformity in the first and second months of pregnancy. Conclusion Exposure to common air pollutants increases the risk of birth defects, and SO2 significantly affects the occurrence of birth defects in the first two months of pregnancy.